Diamond-like Carbon Thin Film Coating for Application on Heterojunction Solar Cells by ECR-CVD System - Tanawit Srisantirut; Weera Pengchan; Toempong Phetchakul (My University, 2020)
Abstract Diamond-like Carbon (DLC) film has the ability to change the refractive index value achieved high transmittance for potential applications of antireflection coating. DLC films were deposited on heterojunction solar cells by the ECR-CVD (Electron Cyclotron Resonance Chemical Vapor Deposition) method using Acetylene (C 2 H 2 ) and Argon (Ar) gases. DLC coating affects ITO (Indium tin oxide), causing the electrical and resistivity of heterojunction solar cell vary according to the coating time. The surface and thickness of the DLC films was measured with an atomic force microscope. Illuminated I-V characteristic was investigated by photo-I–V measurements. The suitable acetylene anti-reflection deposition time at 0.40 minutes. Therefore, heterojunction solar cell was fabricated on a substrate using the optimized DLC films as an anti-reflection coating and it obtained an increase efficiency of about 1%.
Keywords: Electron cyclotron resonance; Diamond-like carbon; Anti-reflective coating; Indium tin oxide; Diamond and Carbon-based Materials Research